2017
DOI: 10.3390/ijms18081693
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Therapy Decreases Incidents of Intracranial Hemorrhage in Mice after Whole-Body Ionizing Irradiation Combined with Burn Trauma

Abstract: Nuclear industrial accidents and the detonation of nuclear devices cause a variety of damaging factors which, when their impacts are combined, produce complicated injuries challenging for medical treatment. Thus, trauma following acute ionizing irradiation (IR) can deteriorate the IR-induced secondary reactive metabolic and inflammatory impacts to dose-limiting tissues, such as bone marrow/lymphatic, gastrointestinal tissues, and vascular endothelial tissues, exacerbating the severity of the primary injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…The latter induces side effects including appetite loss and edema [ 55 ]. Ghrelin administration accelerates body weight recovery and is found no edema [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter induces side effects including appetite loss and edema [ 55 ]. Ghrelin administration accelerates body weight recovery and is found no edema [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that human ghrelin decreased organ injury and increased survival by 30% above the vehicle-treated mice after RI combined with severe sepsis in rats [ 14 ]. Kiang et al [ 24 ] reported that ghrelin therapy was efficacious in a mouse model of radiation combined with wound or burn by increasing survival, body weight, wound healing, bone marrow cell counts, neutrophil recovery and platelet recovery on day 30 post CI as well as inhibiting brain hemorrhage [ 31 ]. Ghrelin blocks NF-κB activation, decreased TNF-α and IL-6 concentrations in lung of septic rats and inhibited nucleotide-binding oligomerization domain-containing protein 2 [NOD2, also known as caspase recruitment domain-containing protein 15 (CARD15) or inflammatory bowel disease protein 1 (IBD1)] [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 Our laboratory recently reported that brain hemorrhage was observed on days 13-16 after irradiation in an experimental animal model of radiation combined with burn trauma. 24 In that report, when mice were exposed to 15% total skin surface burn following 9.5 Gy 60 Cobalt-γ photon radiation, extracranial hemorrhage and intracranial hemorrhage were found. Extracranial hemorrhage was observed in the olfactory lobe, mid-brain, and cerebellum.…”
Section: Introductionmentioning
confidence: 95%
“…Peptides are an important topic in the biomedical field and have been extensively proven to be an ideal therapeutic strategy for many diseases [ 1 , 2 ]. Peptides are used in the treatment of cancers [ 3 ], diabetes [ 4 ], and cerebrovascular disorders [ 5 ]. However, they are easily cleaved by circulating proteases and thus are short-lived [ 6 ].…”
Section: Introductionmentioning
confidence: 99%